COGNITIVE RADIO IN THE ELECTRONIC WARFARE - Galindo Mier, Rafael (Telemática, 2020)
Electronic warfare (EW) includes all actions that use electromagnetic or directed energy weapons to control the electromagnetic spectrum or to attack a threat. Conducting EW in urban areas seeks to achieve much the same results as in other environments. A major consideration in urban areas is collateral effects on portions of the urban critical infrastructure that rely on the electromagnetic spectrum for service. While the EW cognoscenti have long recognized the importance of the contribution of EW to modern warfare, recently EW has been sagaciously integrated into modern warfare thinking. Cognitive radio (CR) technology has been proved to be a tempting solution to promote spectrum efficiency and relieve spectrum scarcity problems. Nevertheless, the cognitive capability cannot only be realized by monitoring on some frequency bands of interest but also more innovative techniques are required to capture the spectrum holes with temporal, frequency or spatial variations in sophisticated frequency hopping spread spectrum (FHSS) radio environments, and avoid to the existing primary users (PU). The aim of this paper is to give an update over view of the roll of CR in EW.